Can Modal Agnosticism Save Constructive Empiricism? (Aporia, 2020)
In this paper I argue that by adopting modal agnosticism, the constructive empiricist can overcome the scientific realist’s main objection. After introducing Bas van Fraassen’s constructive empiricism and showing how he can respond to three traditional objections to his view, I consider James Ladyman’s recent critique. Ladyman correctly argues that the constructive empiricist needs to distinguish between the observable and unobservable in a non-arbitrary manner. To be able to do so, the constructive empiricist must recognise objective modality in nature, but doing so would be at odds with the position’s principle motivation of doing away with inflationary metaphysics and objective modality. I next explain John Diver’s modal agnosticism. I argue that the modal agnostic has the resources available for the constructive empiricist to be able to make the distinction Ladyman requires. Since modal agnosticism does not entail an inflationary metaphysics, I argue that it is compatible with, and can thus save, constructive empiricism from Ladyman’s challenge.